Investigation of strain induced effect on linear shape fiber Bragg grating embedded in composite material - Szeląg, Mateusz; Lesiak, Piotr; Budaszewski, Daniel; Chychłowski, Miłosz; Woliński, Tomasz (Photonics Letters of Poland, 2016)
In this work experimental results are presented of strain induced effects on a linear shape fiber Bragg grating embedded in a composite material. Mechanical analysis of the composite material has been numerically performed by using commercially available software Ansys. Advanced Bragg gratings make it possible to simplify detection systems, calibration process of fiber optic sensors and quasi – spot metering. Full Text: PDF References P. Kisała, "Optoelectronic sensor for simultaneous and independent temperature and elongation measurement using Bragg gratings", Przegląd Elektrotechniczny 11a, 343 (2012). DirectLink X. Wen, D. Zhang, Y. Qian, J. Li, N. Fei, "Improving the peak wavelength detection accuracy of Sn-doped, H2-loaded FBG high temperature sensors by wavelet filter and Gaussian curve fitting", Sensors Actuat. A: Phys. 174, 91 (2012). CrossRef H. Peng, Y. Su, Z. Ye, B. Zhou, "A novel fiber Bragg grating sensor for weak pressure measurement based on the Stokes parameter", Opt. Fiber Technol. 18(6), 485 (2012). CrossRef G. Luyckx, E. Voet, N. Lammens, J. Degrieck, "Strain Measurements of Composite Laminates with Embedded Fibre Bragg Gratings: Criticism and Opportunities for Research", Sensors 11, 384 (2011). CrossRef S. Yashiro, N. Takeda, T. Okabe, H. Sekine, "A new approach to predicting multiple damage states in composite laminates with embedded FBG sensors", Composites Science Technol. 65, 659 (2005). CrossRef Y. Zhan, L. Li, F. Yang, K. Gu, H. Wu, M. Yu, "An all-fibre multi-parameter sensor for composite structures based on a chirped fibre Bragg grating", Opto-Electron. Rev. 21(3), 283 (2013). CrossRef Y. Okabe, R. Tsuji, N. Takeda, "Application of chirped fiber Bragg grating sensors for identification of crack locations in composites", Composites: Part A 35, 59 (2004). CrossRef S. Yashiro, T. Okabe, N. Toyama, N. Takeda, "Monitoring damage in holed CFRP laminates using embedded chirped FBG sensors", Intern. J. Solids Structur. 44, 603 (2007). CrossRef C. Fernandez-Valdivielso, I.R. Matoas, F.J. Arregui, "Simultaneous measurement of strain and temperature using a fiber Bragg grating and a thermochromic material", Sensors Actuat. A: Phys. 101, 107 (2002). CrossRef A. Makovec, G. Berruti, M. Consales, M. Giordano, P. Petagna, S. Buontempo, G. Breglio, Z. Szillasi, N. Beni, A. Cusano, "Radiation hard polyimide-coated FBG optical sensors for relative humidity monitoring in the CMS experiment at CERN", J. Instrumentation 9(3), C03040 (2014). CrossRef P. Kisała, "Detection of material defects with indirect metod by determining the linear expansion with FBG sensor", Przegląd Elektrotechniczny, NR 1a, R. 89, 29 (2013). DirectLink A. Papantoniou, G. Rigas, N.D. Alexopoulos, "Assessment of the strain monitoring reliability of fiber Bragg grating sensor (FBGs) in advanced composite structures", Composite Structur. 93, 2163 (2011). CrossRef Y. Okabe, R. Tsuji, N. Takeda, "Application of chirped fiber Bragg grating sensors for identification of crack locations in composites", Composites: Part A 35, 59 (2004). CrossRef P.Lesiak, M.Szeląg, D.Budaszewski, R.Plaga, K.Mileńko, G.Rajan, Y.Semenova, G.Farrell, A.Boczkowska, A.Domański, T.Woliński, Influence of lamination process on optical fiber sensors embedded in composite material", Measurement, Vol. 45, Issue 9, November 2012, Pages 2275–2280. CrossRef P. Lesiak, M. Szeląg, K. Mileńko, T. Woliński, A. Domański, K. Jędrzejewski, A. Boczkowska, "Polarimetric and Bragg Optical Fiber Sensors for Stress Distribution and Temperature Measurements in Composite Materials", Acta Phys. Polonica A 120, 698 (2011). CrossRef A.W. Domański, P. Lesiak, K. Milenko, A. Boczkowska, D. Budaszewski, S. Ertman, T.R. Woliński, "Temperature-insensitive fiber optic deformation sensor embedded in composite material", Photon. Lett. Poland 1(3), 121 (2009). CrossRef